The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1983
DOI: 10.1017/s0033291700050881
|View full text |Cite
|
Sign up to set email alerts
|

Electrolyte and other physiological abnormalities in patients with bulimia

Abstract: SYNOPSISThe frequencies of various forms of eating-related behaviour (such as vomiting and laxative abuse) are reported for a series of non-anorectic bulimia patients seen for evaluation in an eating disorders clinic. The results of serum electrolyte, glucose and other screening tests in these patients are presented. Electrolyte abnormalities were found in 82 of the 168 patients (48·8%) who were diagnosed as having either bulimia or atypical eating disorder. The most common abnormality was metabolic alkalosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
1

Year Published

1985
1985
2001
2001

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(57 citation statements)
references
References 14 publications
(13 reference statements)
2
54
1
Order By: Relevance
“…Thus, our results might partly be explained by the fact that the subjects were of normal weight. An additional explanation is the fact that, although our population was engaged in self-induced vomiting, the frequency of this behavior was less than reported in some earlier studies (Mitchell et al, 1983;Jacobs & Schneider, 1985). Therefore, previous reports on the prevalence of electrolyte abnormalities in patients with BN might have been affected by sampling bias due to the higher severity of these clinical characteristics in patients seeking treatment in special care settings.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Thus, our results might partly be explained by the fact that the subjects were of normal weight. An additional explanation is the fact that, although our population was engaged in self-induced vomiting, the frequency of this behavior was less than reported in some earlier studies (Mitchell et al, 1983;Jacobs & Schneider, 1985). Therefore, previous reports on the prevalence of electrolyte abnormalities in patients with BN might have been affected by sampling bias due to the higher severity of these clinical characteristics in patients seeking treatment in special care settings.…”
Section: Discussioncontrasting
confidence: 53%
“…Some studies (Pyle, Mitchell, & Eckert, 1981;Jacobs & Schneider 1985;Greenfeld et al, 1995) show modest prevalence rates of electrolyte and other serum abnormalities, whereas others report much higher rates (Mitchell, Pyle, Eckert, Hatsukami, & Lentz, 1983;Hall et al, 1989;Biebl & Kinzl, 1996). Serious blood serum abnormalities appear to be more prevalent among patients with low weight, frequent selfinduced vomiting, and laxative abuse.…”
Section: Introductionmentioning
confidence: 99%
“…In four studies the prevalence of laxative abuse among individuals with bulimia nervosa ranged from 38 to 63% [1][2][3][4], While laxatives reduce caloric absorption only by approxi mately 12% [5], patients with eating disorders often describe a sense of purging excess food. Indeed, the volume depletion and accompa nying nausea may cause them to feel unwell and diminish appetite.…”
Section: Introductionmentioning
confidence: 99%
“…The frequency of hypokalemia for patients in the current study is similar to the 5.5% rate reported by Greenfeld, Mickley, Quinlan, and Roloff (1995) in eating disorder outpatients. However, some studies have reported an absence of hypokalemia in bulimic patients (Peeters & Meijboom, 2000;Pyle, Mitchell, & Eckert, 1981) whereas others have observed hypokalemia in up to 55% of patients (Crow, Salisbury, Crosby, & Mitchell, 1997;Hall et al, 1989;Mira, Stewart, Vizzard, & Abraham, 1987;Mitchell et al, 1983Mitchell et al, , 1987Palla & Litt, 1988;Russell, 1979). Variability in results across studies is most likely to reflect changes over time in diagnostic nosology, wide differences in sample characteristics (e.g., body weight, symptom severity, method of purging), and the potential influence of psychiatric and medical comorbidity.…”
Section: Discussionmentioning
confidence: 99%